Enhancing Flowering in Vanilla (Vanilla planifolia L.) 'Vania 1' Using Jakaba Fungi and Coconut Water - Anastasia Fara Aireza; Sandra Arifin Aziz; Diny Dinarti (Journal of Tropical Crop Science, 2026)
Flowering is a crucial phase in vanilla (Vanilla planifolia) cultivation, heavily influenced by environmental conditions and cultivation practices. This study investigates the combined effects of Jakaba fungi and coconut water, a natural source of plant hormones, on vanilla flowering. The experiment followed a completely randomized block design with 12 treatment combinations and three replications. Each treatment used two plants, with five untreated controls and five plants treated with farmer standard Jakaba application, for a total of 82 plants. Coconut water was applied at 50, 100, and 150 ml per plant, while Jakaba was used at 150, 200, and 250 ml per plant. The optimal combination—200 ml of Jakaba with 50 ml of coconut water—resulted in the highest flowering and fruiting response. These findings highlight the potential of integrating Jakaba and coconut water to boost vanilla productivity.